Urethral Plate Characteristics in Cases of Non-proximal Hypospadias May Not Be Associated With a Higher Risk of Complications When a Two-Stage Repair Is Applied - Marcou, Marios; Bobbe, Sarah-Magdalena; Wullich, Bernd; Hirsch-Koch, Karin (Frontiers in Pediatrics, 2022)
Purpose To investigate whether a two-stage repair of distal- and mid-shaft hypospadias (non-proximal hypospadias) could eliminate the risk factors resulting from adverse urethral plate characteristics and eventually reduce complication rates. Methods We retrospectively reviewed all cases of primary surgical repair of non-proximal hypospadias performed in our center between 2009 and 2018. In all cases where adverse urethral plate characteristics were found, such as meatal stenosis, a shallow urethral groove, a thick web of tissue between the native meatus and the urethral groove or in the presence of a very “thin,” skin-like distal urethra, a two-stage repair was routinely undertaken. In cases of native meatal stenosis, a meatotomy, and meatoplasty were performed. In cases of a very “thin” distal urethra we incised the skin proximally up to the point of a normal urethral fold and a meatoplasty was performed at that point. Hypospadias repair was then performed in a second operation, 3–6 months following the first procedure. Urethroplasty, both in cases of a single-stage repair and in cases of a two-stage repair, was always performed using the Thiersch-Duplay technique. Patients with a follow-up of less than 12 months were excluded from this study. Results Over a period of 10 years, 208 boys underwent primary surgical repair of non-proximal hypospadias. Eighty-nine of the 208 patients (42.8%) underwent single-stage hypospadias repair. Two-stage repair of the hypospadias was required in 119 (57.2%) of the patients. The overall complication rate was 3.4% in the group operated in a single stage and 7.6% in the group that required a two-stage repair (p = 0.09). The most frequent complication reported was urethrocutaneous fistula (p = 0.31), followed by meatal stenosis (p = 0.37), urethral stricture (p = 0.08) and wound dehiscence (p = 0.16). There was no significant difference between the complication rates of the two groups. Conclusion Patients with distal hypospadias and poor urethral plate characteristics repaired in a two-stage approach have comparable low-complications to those with favorable urethral plate characteristics repaired in a single-stage.